Efektifitas Edukasi Self Care Management Terhadap Perilaku Kepatuhan Pengendalian Hipertensi Pada Pasien Hipertensi di Rumah Sakit Primaya Hospital Bekasi Utara - Achmad Fauzi; Alika Putri (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Hypertension has become one of the important health problems and the most common vascular disease in developed countries, and specifically in developing countries. Hypertension is referred to as a degenerative disease and a non-communicable disease; this condition often occurs and has a relatively high mortality rate, as well as affecting the quality of life and productivity of individuals. Providing self-management education can also enhance patients' abilities to manage the signs and symptoms that arise, improve cognitive, behavioral, and emotional responses necessary to maintain quality of life, thus preventing complications and minimizing the disturbances caused in bodily functions, emotions, and interpersonal relationships with others that can disrupt the client's life. Objective: To determine the Effectiveness of Self-Care Management Education on Adherence Behaviors in Managing Hypertension in Hypertensive Patients at Primaya Hospital Bekasi Utara. Method: This research is a quantitative study using Quasi-Experimental research methods with the technique employed being Two Group Pre Test-Post Test Control Group Design. The sample in this study was taken from all hypertensive patients receiving outpatient care in the Internal Medicine Clinic at Primaya Hospital Bekasi Utara. Thus, there are 17 patients for the intervention group and 17 patients for the control group. Results: The analysis of the chi-square test showed that in the control group, a p-value of 0.010 was obtained (<α 0.05). This means that there is a significant effect in the control group that did not receive treatment. In the analysis of the chi-square test in the intervention group, a p-value of 0.012 was obtained (<α 0.05). This means that there is a significant influence on the intervention group that received the treatment. Conclusion: Self Care Management education affects hypertension control behavior in hypertensive patients. Suggestion: The research results can serve as a discussion material to continue developing and implementing effective and efficient educational interventions that can improve health behavior changes for the better.